ANALISIS KINERJA KEUANGAN PERUSAHAAN DAERAH JASA TRANSPORTASI KOTA BOGOR - Nurhayati, Immas; Suharti, Titing; Rivai, Novan Mushaf (inovator, 2016)
Perusahaan Daerah Jasa Transportasi (PDJT) is one of the regional-owned enterprises engaged in transportation services especially for Bogor community. Provision of transportation services for the community is one kind of improved services for the community, instead of increasing government revenue. The analysis showed that during the first trimester ( January to March 2014), financial performance of PDJT is not good. At that period, the company is liquid, but that liquidity is not driven by the good performance of the company, but due to the injection of capital from a government. During that period, the company is unprofitable, can’t gain revenue and profit. This is caused by high operating expenses and the lack of efficient use of company funds.